Synthesis, characterization and 59Co NMR study of novel Co(III) complexes with selected N-acyl-N’,N’-dialkylthiourea ligands: an assessment of spontaneous metathesis by multinuclear NMR spectroscopy and rp-HPLC - Barnard, Ilse (2016)
Thesis (MSc)--Stellenbosch University, 2018.